Surface Groundwater Pollution Dynamics Over 2015-2020 in the Salt Drying Pond of Pademawu Subdistrict, Madura, Indonesia - Wisnu Arya Gemilang; Ulung Jantama Wisha; Mas Agus Mardyanto (Geosfera Indonesia, 2022)
Pamekasan coastal area is the center of salt production concentrated in the Pademawu subdistrict with the ponds area of 740.96 ha. The sufficiently close distance of salt ponds to settlement areas allows several issues, such as shallow groundwater salinization. This study aimed to determine the salt pondâ€™s degradation over five years (2015-2020) and its influence on the salinization issue in Pademawu. We compare groundwater quality parameters (conductivity, TDS, the depth of shallow surface groundwater, and salinity) surveyed in 2015 and 2020, correlated to salt pond area alterations. Over five years of measurement, it was found that conductivity declined, reaching 2779.94 ÂµS/cm. Based on TDS deterioration, groundwater transformed from brackish to freshwater in 2020. By contrast, the depth of shallow groundwater-surface increased by almost one meter. The freshwater area also increased by 22% over five years based on conductivity classification. Groundwater quality dynamics are related to the alteration of the salt pond area. On the other hand, the significant increase in rainfall intensity, which is not beneficial for salt agriculture, results in the salt pond area deterioration, thereby declining surface groundwater salinity in Pademawu due to the less interaction between Cl and groundwater within aquifers. Although the groundwater pollution induced by seawater intrusion and salinization declined in 2020, re-organizing the distance between salt ponds and the settlement area in Pademawu is crucial to minimize further groundwater pollution. Keywords : Dynamics; pollution; groundwater; salt agriculture; Pademawu Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License